CONTENT AS A GROWTH ENGINE: MANAGING STRATEGY, PRODUCTION, AND DISTRIBUTION AT SCALE - Erlina Desi Purwanti; Lukmanul Hakim; Dahrul Aman Harahap (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
In the digital economy, content has evolved from a marketing tactic to a core driver of customer acquisition, engagement, and revenue. However, scaling content operations effectively presents significant strategic and operational challenges. This study investigates how organizations can systematically manage content as a scalable growth engine. The objective is to develop an integrated framework for aligning content strategy with business objectives, optimizing production workflows, and mastering multi-channel distribution. Employing a qualitative multiple case study methodology, the research analyzed in-depth interviews with 38 content leaders and practitioners across seven high-growth companies. The results identify three critical pillars: a documented strategic "content architecture," industrialized yet agile production processes, and a data-informed, omnichannel distribution model. The discussion reveals that successful scaling requires a shift from project-based creation to a product management mindset, supported by cross-functional teams and robust technology infrastructure. It is concluded that treating content as a perpetual growth engine demands strategic orchestration across the entire lifecycle, transforming content from a cost center into a measurable, scalable asset that fuels sustainable business expansion.